Telomeres are shorter in Portuguese obese adults - Duarte, Catarina (2024)
Obesity is a clinical condition characterized by an abnormal accumulation of adipose tissue with an increased risk of developing illnesses such as type 2 diabetes, cardiovascular disease, and cancer. In obesity, the secretion of proinflammatory adipokines contributes to oxidative stress that can lead to a decline in the length of telomeres. Telomeres are structures of repetitive sequences delimiting the chromosomes, that play a crucial role in maintaining their integrity and stability and, thus, their shortening is associated with cellular senescence and possible apoptosis. Although some studies indicate that obesity is associated with shorter telomeres, others contradict this data. Accordingly, our study aimed to determine whether obesity is associated with telomere shortening in Portuguese obese adults. For that, we collected buccal epithelial cells from 72 obese (Body Mass Index (BMI) greater than 30 kg / m2) and 74 norm-weight individuals (BMI between 18.5 kg / m2 and 24.99 kg / m2) and determined telomere length through Real-Time PCR. Results revealed that the relative telomere length of obese individuals is statistically significantly shorter than that of the control non-obese group. By comparing obese subgroups, it was possible to observe that in the female subgroup, the relative length of telomeres was shorter, in opposition to the male obese group, which indicates that the association between high BMI and shorter telomeres is genre-dependent. Furthermore, by studying the telomere length by age it was observed that there was no difference in the relative telomere length in obese under versus over 45 years old, demonstrating an age-independent association between obesity and telomere length. Accordingly, our results suggest that obesity is associated with telomeres shortening and that this could be used as a biomarker in obesity.